2021
DOI: 10.1097/j.pain.0000000000002452
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane protein TMEM184B is necessary for interleukin-31–induced itch

Abstract: Supplemental Digital Content is Available in the Text.Transmembrane protein 184B is necessary for the proper function of itch-sensitive sensory neurons involved in eczema through the control of Wnt pathway gene expression during development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…To evaluate common signatures of TMEM184B-dependent gene expression across disparate types of neurons, we compared the differentially expressed genes (Adjusted p < 0.05) between our 5 month hippocampus data set and one we have previously reported from 6 month adult dorsal root ganglia [10]. Among differentially expressed genes, we identified 12 genes (including Tmem184b itself) that were similarly regulated (Figure 5 and Additional File 8).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate common signatures of TMEM184B-dependent gene expression across disparate types of neurons, we compared the differentially expressed genes (Adjusted p < 0.05) between our 5 month hippocampus data set and one we have previously reported from 6 month adult dorsal root ganglia [10]. Among differentially expressed genes, we identified 12 genes (including Tmem184b itself) that were similarly regulated (Figure 5 and Additional File 8).…”
Section: Resultsmentioning
confidence: 99%
“…Bhattacharya et al 22 found that TMEM184B is highly expressed in the nervous system with axon degeneration and neuromuscular junction maintenance in mice, suggesting that TMEM184B strongly influences the regulation of axonal degeneration and peripheral nervous system morphology and function. Larsen et al 23 found that TMEM184B promoted adult somatosensation through developmental Wnt signalling pathway. Rasmussen et al 24 noted that TMEM184B might regulate ibuprofen uptake by type I cells of Madin‐Darby canine kidneys (MDCK) under hyperosmotic conditions and was regulated by the transcription factor Nfat5.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Previous studies have confirmed that several proteins in the TMEM family are abnormally found that TMEM184B is highly expressed in the nervous system with axon degeneration and neuromuscular junction maintenance in mice, suggesting that TMEM184B strongly influences the regulation of axonal degeneration and peripheral nervous system morphology and function. Larsen et al 23…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cutaneous and intrathecal injections of IL-31 evoked intense itch, which was TRPV1 and TRPA1-dependent [113]. Moreover, a more recent study showed that transmembrane protein 184B (TMEM184B) is necessary for IL-31-induced itch [116]. Thus, the details of the mechanism of IL-31-induced itch are becoming clearer, and target molecules that can lead to treatment are being identified one after another.…”
Section: Il-31mentioning
confidence: 99%